Corrosion Protection of SAE 1020 Steel Using CeO2 Coatings Prepared Via Ionic Liquid Method - Thácylla J.M. de Jesus; João B. R. Carvalho; Katlin I. B. Eguiluz; Giancarlo R. Salazar-Banda (Materials Research)
Corrosion of SAE 1020 carbon steel, extensively used in the petrochemical industry, remains a persistent challenge. Replacing toxic chromate-based coatings with sustainable alternatives is equally critical. This study introduces an innovative, environmentally friendly surface modification method using the thermal decomposition of cerium chloride heptahydrate (CeCl3·7H2O) dissolved in the ionic liquid 1-methylimidazolium hydrogen sulfate, a non-toxic solvent not previously used for the deposition of anticorrosion protective coatings. Coatings were calcined at temperatures from 400 to 600 °C. Electrochemical analyses revealed that the coating treated at 550 °C exhibited the highest corrosion resistance, even after prolonged immersion in corrosive media. This outcome was attributed to the formation of a dense, homogeneous, and adherent CeO2 layer. The method proved effective in forming protective CeO2 films, confirming the potential of ionic liquids in producing high-performance anticorrosion coatings. Thus, the developed approach represents a promising and sustainable alternative for corrosion protection in demanding industrial environments, particularly within the oil and gas sector.